ПРОБЛЕМА МЕНТАЛЬНОЙ ПРИЧИННОСТИ (Philological Studies, 2019)
The author is concerned with the problem of mental causation. Although ontological physicalists hope to avoid it, they can not escape a version of it. Different solutions are presented and critically analysed, especially the causal exclusion argument. Non-reductionisms face the dilemma: reduction of mental properties to physical properties and thus preservation of causal powers of the mental, or, if reduction is not possible, acceptance of epiphenomenalism.